1994
DOI: 10.2190/f3m1-8kay-lbf3-gdpq
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Associated with Substance Abuse among Secondary School Students in Trinidad and Tobago

Abstract: This study attempts to investigate factors associated with involvement in substance abuse in Trinidad and Tobago, through a survey of 1603 secondary school students, aged fourteen to eighteen years. Analysis of the data using the Chi-square test indicates a significant association (p < .001) between involvement in substance abuse and the following factors: grades at school, importance of religious involvement, amount of spending money obtained, confidence placed in parents/peers, parental involvement in alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 2 publications
1
15
0
4
Order By: Relevance
“…Studies in other countries have shown associations between money availability and drug use. 12,16 There was a linear increase in the prevalence of drug use with age, but no significant differences with respect to sex. Consumption differences between boys and girls appear when different substances are evaluated in separate, but disappear when drugs are grouped.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Studies in other countries have shown associations between money availability and drug use. 12,16 There was a linear increase in the prevalence of drug use with age, but no significant differences with respect to sex. Consumption differences between boys and girls appear when different substances are evaluated in separate, but disappear when drugs are grouped.…”
Section: Discussionmentioning
confidence: 89%
“…Drug and alcohol use by parents were also identified as predictive factors in other studies. 12,16 The fact of having a drug user at home may already be an indicator of family disorders predisposing to drug use. Moreover, the greater proportion of addicts in certain families may suggest an effect of genetic factors on modulating susceptibility to addiction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations